Special Types of Pesticides - Frederick M. Fishel (EDIS)
This guide discusses some unique materials that are used as pesticides. Some types of pesticides do not belong to any specific chemical groups. Some of these are synthetically manufactured; some occur naturally in the environment, and others are produced by living organisms. These pesticides include antibiotics, anticoagulants, botanicals, insect dusts, insect growth regulators, microbials, petroleum oils, pheromones, plant hormones, and soaps. This document is PI-47, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.